PICTURE BOOK ON RAISING CHILDREN’S AWARENESS AGAINST SEXUAL ABUSE - Evelyn Christy; Priska Febrinia Handojo (Kata Kita: Journal of Language, Literature, and Teaching, 2015)
One of the common problems leading to the sexual abuse is that the child is not aware about it. This project aims to raise children’s awareness against sexual abuse through picture book. This picture book use realistic fiction as the genre of my picture book. The purpose is to make the children familiar with the story and can relate it to their life. This picture book uses the narrative theory as the framework of the story. The narrative story is consist of abstract, orientation, complication, resolution, and evaluation. This picture book tells about a child name Deni, who survives from sexual abuse by his neighbor named Mr. Dodi. The problems start when Mr. Dodi lures Deni to come with him using lollypop. In the climax, Deni shouts for help and runs from Mr. Dodi. Then, he finds his mother and asks her to go home immediately. At the end of the story, Deni’s mom gives Deni more explanation about his private body parts and how to keep it private